2022
DOI: 10.1021/acs.jcim.2c00241
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Accessible Chemical Space of SIRT2 Inhibitors through Exploration of Binding Pocket Dynamics

Abstract: Considerations of binding pocket dynamics are one of the crucial aspects of the rational design of binders. Identification of alternative conformational states or cryptic subpockets could lead to the discovery of completely novel groups of the ligands. However, experimental characterization of pocket dynamics, besides being expensive, may not be able to elucidate all of the conformational states relevant for drug discovery projects. In this study, we propose the protocol for computational simulations of sirtui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 102 publications
1
12
0
Order By: Relevance
“…Early recognition is the direct reflection of the models’ ability to rank active molecules very early in an ordered list. Herein, we used ROC EF 0.5%, 1%, 2%, and 5%, which quantified the area covered by the curve at 0.5%, 1%, 2%, and 5% of the screened false positives, respectively [ 20 , 46 ]. With the dataset containing a significantly larger number of chemically diverse inactive compounds, the RF:ECFP4 binary model stood out as the model with the greatest predictive power ( Table 4 and Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early recognition is the direct reflection of the models’ ability to rank active molecules very early in an ordered list. Herein, we used ROC EF 0.5%, 1%, 2%, and 5%, which quantified the area covered by the curve at 0.5%, 1%, 2%, and 5% of the screened false positives, respectively [ 20 , 46 ]. With the dataset containing a significantly larger number of chemically diverse inactive compounds, the RF:ECFP4 binary model stood out as the model with the greatest predictive power ( Table 4 and Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently described pharmacological advantages of selective SIRT2 inhibition over non-selective inhibition of other isoforms of the sirtuin family, particularly sirtuin 1 (SIRT1) and sirtuin 3 (SIRT3), positioned selectivity as one of the most important objectives in development of novel SIRT2 inhibitors [ 19 ]. Furthermore, a recent study indicated that the complex conformational behavior of SIRT2 in interaction with inhibitors represents one of the major obstacles in the discovery of novel inhibitors through structure-based computer-aided drug-design (CADD) approaches [ 20 ]. However, years of searching for novel SIRT2 inhibitors resulted in large and diverse datasets that could greatly benefit ligand-based CADD approaches relying on specific machine-learning techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we used ROC EF 0.5%, 1%, 2% and 5% which quantify the area covered by the curve at the 0.5%, 1%, 2% and 5% of the screened false positives. 44,52 With dataset containing significantly larger amount of chemically diverse inactive compounds, RF:ECFP4 binary model stood out as the model with the greatest predictive power (Table 4 and Figure 4). In the heavily disbalanced decoys set, RF:ECFP4 binary model displayed better sensitivity, specificity, precision and robustness but also better early recognition.…”
Section: Binary Classification Modelsmentioning
confidence: 99%
“…The novel structure-based virtual screening (SBVS) approach relying on alternative conformational states of SIRT2 discovered through computationally intensive simulations of the binding pocket dynamics was recently published by our group. 44 Utilization of alternative binding pocket conformational states, besides showing significant improvements in validation metrics compared with single structure approach, resulted in expansion of chemical space coverage of virtual hits. In order to test SIRT2i_Predictor's ability to expand the chemical space of virtual hits, we have repeated prospective SBVS campaign from the mentioned paper encompassing around 200000 compounds from the SPECS database.…”
Section: Benchmarking Sirt2i-finder Against Structure-based Vs Approachmentioning
confidence: 99%
See 1 more Smart Citation